The Effect of Everyone is a Teacher Here Model and Self-Regulated Learning Towards Learning Outcomes of Indonesian History - Rinaldo Adi Pratama; Nurzengky Ibrahim; Sarkadi Sarkadi (Jurnal Pendidikan Indonesia, 2019)
This research aimed at finding the influence of the learning model Everyone Is a Teacher Here and Self-Regulated Learning towards of Learning Outcomes of Indonesia History. The research was conducted at SMAN 8 Tangerang on the academic year 2017/2018. The research method was experiment, with treatment by level 2X2. Results showed that the students who were treated with the Everyone Is a Teacher Here model had high learning outcomes, compared to those who were given direct model learning; groups of students who had high self-regulated learning and they received learning Everyone Is a Teacher Here had a higher learning outcomes in Indonesian history compared to those given direct learning; groups of students who had low Self-Regulated Learning and they received direct learning, haved higher learning outcomes in Indonesian history compared to those studied Everyone Is a Teacher Here; and, ultimately, there was an interaction effect between the learning model and the Self-Regulated Learning of the learning outcomes of Indonesian history.